Pengaruh Servant Leadership terhadap Mutu Layanan Pendidikan di MTs Miftaahush Shuduur Kecamatan Ciampea Kabupaten Bogor - Muhamad Robie Awaludin S; Seno Aji Nurmansah (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2021)
Education Quality Service is an educational service capable of producing graduates who have expertise and competence as an advantage that is well-organized starting from input, process and output. Based on education quality indicators which include input, process and output . This study aims to explain 1) Describe the picture of servant leadership in MTs. Miftaahush Shuduur, 2) Describe how the quality of education services in MTs is described. Miftaahush Shuduur, 3) Analyzing the effect of servant leadership on the quality of education services at MTs. Miftaahush Shuduur. This research was conducted at MTs Miftaahush Shuduur, Ciampea District, Bogor Regency. Based on the results of the analysis, it was found that servant leadership simultaneously has a positive effect on the quality of education services. This shows that the stronger the influence of servant leadership , the higher the quality of educational services produced by the institution. Therefore, to establish the quality of educational services in institutions, it is expected that more attention is paid to a servant leadership style . Keywords: Servant Leadership ; Quality of Education Services .